Stakeholder pressure and the adoption of environmental practices: The mediating effect of training - Sarkis, Joseph; Gonzalez‐Torre, Pilar; Adenso‐Diaz, Belarmino (Journal of Operations Management, 2010)
AbstractThe influence of stakeholder pressure on the adoption of environmental practices has been established in the literature. In this paper we posit that these direct effects are further mediated, causally, by the level of training in companies. Theoretically, this relationship is supported by the relationship between institutional theory (stakeholder pressure) and the dimensions of dynamic capabilities in resource‐based theory. We investigate this relationship within the Spanish automotive industry. The theoretical contribution of this paper focuses on further supporting the relationship between stakeholder and resource‐based theory as complementary theoretical frameworks. The practical implications focus on whether or not training should be integrated in order to help in the adoption of particular environmental practices, which in this study are represented by environmentally oriented reverse logistics practices.